2018
DOI: 10.1101/371096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling Cellular Resource Allocation Reveals Low Phenotypic Plasticity of C4 Plants and Infers Environments of C4 Photosynthesis Evolution

Abstract: Summary-The regulation of resource allocation in biological systems observed today is the cumulative result of natural selection in ancestral and recent environments. To what extent are observed resource allocation patterns in different photosynthetic types optimally adapted to current conditions, and to what extend do they reflect ancestral environments? Here, we explore these questions for C3, C4, and C3-C4 intermediate plants of the model genus Flaveria.-We developed a detailed mathematical model of carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
3
0
0
Order By: Relevance
“…Our modelling efforts provide an explanation for the observed variation in J atpmax / V cmax and V pmax / V cmax , and why V pmax / V cmax in C 4 appears to be optimized for the lower bounds of atmospheric CO 2 of the Pleistocene (~200 ppm) (Figure 3, Supporting Information: Figure and ). Our reported values of V pmax / V cmax are comparable with previous studies (Kubien et al, 2003; Pengelly et al, 2010; Pignon & Long, 2020; Yin et al, 2016), and two recent papers also indicated that the coordination between CB and C 4 cycles is more appropriate for low CO 2 conditions (Pignon & Long, 2020; Sundermann et al, 2018). All extant C 4 species have gone through a low CO 2 bottleneck over the last 5 million years (Edwards et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our modelling efforts provide an explanation for the observed variation in J atpmax / V cmax and V pmax / V cmax , and why V pmax / V cmax in C 4 appears to be optimized for the lower bounds of atmospheric CO 2 of the Pleistocene (~200 ppm) (Figure 3, Supporting Information: Figure and ). Our reported values of V pmax / V cmax are comparable with previous studies (Kubien et al, 2003; Pengelly et al, 2010; Pignon & Long, 2020; Yin et al, 2016), and two recent papers also indicated that the coordination between CB and C 4 cycles is more appropriate for low CO 2 conditions (Pignon & Long, 2020; Sundermann et al, 2018). All extant C 4 species have gone through a low CO 2 bottleneck over the last 5 million years (Edwards et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Figure S5 and S8). Our reported values of V pmax /V cmax are comparable with previous studies (Kubien et al, 2003;Pengelly et al, 2010;Pignon & Long, 2020;Yin et al, 2016), and two recent papers also indicated that the coordination between CB and C 4 cycles is more appropriate for low CO 2 conditions (Pignon & Long, 2020;Sundermann et al, 2018). All extant C 4 species have gone through a low CO 2 bottleneck over the last 5 million years…”
Section: Discussionsupporting
confidence: 90%
“…Our modeling efforts provide an explanation for the observed variation in J max / V cmax and V pmax / V cmax , and why V pmax / V cmax appears to be optimized for the lower bounds of atmospheric CO 2 of the Pleistocene. Our reported value of V pmax / V cmax are comparable with previous studies (Kubien et al , 2003; Pengelly et al , 2010; Yin et al ,2011, 2016; Pignon and Long, 2020), and two recent papers also indicated that the coordination between CB and C 4 cycles might represent a legacy of ancient low CO 2 conditions (Sundermann et al, 2018; Pignon and Long, 2020). All extant C 4 species have gone through a low CO 2 bottleneck over the last 5 million years (Edwards et al, 2010).…”
Section: Discussionsupporting
confidence: 91%